ASSESSING THE IMPACT AND CHALLENGES OF ENGLISH AS A MEDIUM OF INSTRUCTION IN INDONESIAN HIGHER EDUCATION: A PATHWAY TO GLOBAL INTEGRATION OR A BARRIER TO LOCAL IDENTITY? - Numan, Muhammad; Ayaz, Maria (Transpublika Publisher, 2024)
This research examines the effect of the implementation and implication of English as Medium of Instruction in Indonesian higher education institutions. It further examines the impact of EMI on educational outcomes, cultural identification, and the linguistic future. The study assumes both the positive and negative significance of the above measures. Following the qualitative methodology, the case study conducted semi-structured interviews with 30 participants, including 15 faculty members and 15 students, from three diverse universities in Indonesia. The diverse perspectives demonstrate both the positive and negative impacts of EMI. While the research finds a positive correlation between EMI implementation and English proficiency, as well as better global engagement, the study also exposes such hindrances to the EMI as the language proficiency barriers and the issues of cultural displacement and lack of equity. Apart from that, the fears related to the erosion of Bahasa Indonesia and the local identity are also due to the friction between culture preservation in globalization integration. As a result, the policy recommendations are developed with the idea to propose the measures of the transition to the EMI, which does not replace the national educational practices and values.